Pengaruh Straits Times Index, Harga Emas Dunia, Dan Inflasi Terhadap Ihsg Di Bursa Efek Indonesia Periode 2018 – 2023 - Mohammad Rizky Axell Putranto; Yanda Bara Kusuma (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The aims of this research is to determine and analyze the influence of the Straits Times Index (STI), world gold prices, and inflation on the Indonesia Composite Index on the Indonesia Stock Exchange during the period 2018 - 2023. The population in this research is time series data for 60 months from the ICI price movement on the Indonesia Stock Exchange during the period July 2018 – June 2023. The sampling technique used saturated samples so that the samples obtained were 60. The research method used was multiple linear regression analysis. The results of this research show that 1) the Straits Times Index (STI), World Gold Prices and Inflation simultaneously have a significant effect on the ICI on the IDX for the period 2018 – 2023, 2) the Straits Times Index (STI) partially has a positive effect and significantly to the ICI on the IDX for the period 2018 – 2023, 3) World gold prices partially have a positive and significant effect on the ICI on the IDX for the period 2018 – 2023, 4) Inflation partially has a positive and significant effect on the ICI on the IDX for the period 2018 – 2023 Keywords: Straits Times Index, World Gold Prices, Inflation, ICI